Synthesis, characterization, and biological evaluation of some novel ϒ-aminobutyric acid aminotransferase (GABA-AT) inhibitors - Shrivastava S.K.; Sinha O.; Kumar M.; Waiker D.K.; Verma A.; Tripathi P.N.; Bhardwaj B.; Saraf P. (My University, 2025)
In our present work, some novel substituted 4-phenyl-5-vinylpyrrolidin-2-one derivatives were designed, synthesized, and evaluated for their γ-aminobutyric acid-aminotransferase (GABA-AT) inhibition and in-vivo anticonvulsant activity. Among all the synthesized derivatives, compound 7f was observed as the most potent and competitive inhibitor of GABA-AT (IC50 = 46.29 ± 3.19 µM, Ki = 0.106 ± 0.004 μM). The in-vivo anticonvulsant activity against maximum electroshock (MES) and PTZ, induced seizures test of compound 7f, was observed very significantly (P < 0.05) in comparison with standard Vigabatrin and have shown an increase in the level of GABA in the cortex region of the brain. The ex-vivo studies have also suggested reduced tissue necrosis. Finally, In-silico molecular docking and dynamics studies of compound 7f have shown that it forms desired amino acid residue interactions with the GABA-AT and was stable for 50 ns in the active site pocket of the enzyme. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.